(untitled) (Research, Society and Development, 2022)
The Previne Brasil Program comes as a proposal to modify the financing of the health system and brings great challenges to the public service, since it conditions the transfer of funds to the maximum reach of certain health indicators. It is based on this new reality that affects Primary Health Care, that this study brings a strategic possibility of action so that the teams can articulate and seek ways to achieve the goals established by the Federal Government. This is an experience report, lived by residents during the elaboration and implementation of the Project entitled Qualifica HiperDia. It aims to report the construction and implementation of a line of care for people with chronic conditions, with particular emphasis on Systemic Arterial Hypertension and Diabetes Mellitus. The project emerges as an alternative to reduce the difficulties in the team’s work process in tracking, monitoring and monitoring the health needs of the community related to Chronic non-Communicable Diseases.